Challenging conventional paradigms in applied sports biomechanics research - Glazier, P. S.; ehdizadeh, S (Sports Medicine, 2019)
This paper evaluates the effectiveness of, and highlights issues with, conventional paradigms in applied sports biomechanics research and comments on their capacity to optimise techniques of individual athletes. In empirical studies, group-based analyses often mask variability between athletes and only permit probabilistic `in general` or `on average` statements that may not be applicable to specific athletes. In individual-based analyses, performance parameters typically exhibit a small range and a flat response over iterative performance trials, making establishing associations between performance parameters and the performance criterion problematic. In theoretical studies, computer simulation modelling putatively enables athlete-specific optimum techniques to be identified, but given each athlete`s unique intrinsic dynamics, it is far from certain that these optimum techniques will be attainable, particularly under the often intense psychological pressures of competition, irrespective of the volume of practice undertaken. Sports biomechanists and coaching practitioners are advised to be more circumspect with regard to interpreting the results of applied sports biomechanics research and have greater awareness of their assumptions and limitations, as inappropriate interpretation of results may have adverse consequences for performance and injury.